Northern Aquaculture Enterprise / Mohd Fauzi Mohamad ... [et al.] - Mohamad, Mohd Fauzi; Che Mat Zin, Nasariza; Mohd Sabri, Nur Asma; Duakim, Lucia; Mat Isa, Marlia (2003)
This business will be incorporated on 19 January 2003. The name of the business is Northern Aquaculture Enterprise. We chose this name because it is easy to say and suitable with our company location at Jitra. It is a partnership business type and there are five members involved. We chose this form of business because we believe that each partners will be more responsibility to this business operation and more concern about this business in aiming to get more profit and bonus for the contribution money that they have given. Our Northern Aquaculture Enterprise sells fresh fish to customer, wholesaler and restaurant's owner. Our company operates at Km 21 Jalan Changlun, Sungai Gelung, Kubang Pasu/ Padang Terap, 06000, Jitra, Kedah. It is very strategic because it is near the stream which is make easy for our fish rearing.